2019
DOI: 10.1159/000496165
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Scleral Buckling with a Wide-Field Surgical Microscope and Chandelier Illumination in Retinal Detachment Repair

Abstract: Purpose: To assess treatment efficacy of scleral buckling surgery with wide-field surgical microscope and 27-gauge (G) chandelier illumination for rhegmatogenous retinal detachment (RRD). Methods: This study is a retrospective chart review of 29 eyes in 29 patients with RRD who underwent scleral buckling surgery with a wide-field surgical microscope and 27-G chandelier illumination fiber inserted into the sclera at the pars plana. Results are expressed as mean ± standard deviation. Data were analyzed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…Recently, Frisina et al reported 213 eyes of primary RRD who underwent microscope-assisted ab externo surgery and demonstrated the safety and efficacy of this technique [ 15 ]. However, the reported studies on chandelier endoillumination-assisted scleral buckling cover a limited follow-up period, ranging from 1 to 12 months [ 3 , 16 21 ]. Our group applied 25-gauge cannula-based chandelier-assisted scleral buckling since 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Frisina et al reported 213 eyes of primary RRD who underwent microscope-assisted ab externo surgery and demonstrated the safety and efficacy of this technique [ 15 ]. However, the reported studies on chandelier endoillumination-assisted scleral buckling cover a limited follow-up period, ranging from 1 to 12 months [ 3 , 16 21 ]. Our group applied 25-gauge cannula-based chandelier-assisted scleral buckling since 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The use of EI chandelier-assisted SB technique, as was previously reported, has shown to have similar outcomes compared with conventional indirect ophthalmoscopic SB surgery for primary reattachment. 9 By the way the visualization of the retina through a wide-angle indirect system, pathologies are easier to find, marked, and treated while the surgery may become quicker. With better and, somewhat, easier visualization of the crucial parts of the surgery, the popularity of SB surgery may rise again.…”
Section: Discussionmentioning
confidence: 99%
“…Heutzutage wird die Buckelchirurgie von den meisten Chirurgen auch mikroskopassistiert mit Endoillumination [2] durchgeführt, was eine präzisere Lokalisation der Befunde ermöglicht, jedoch den Nachteil des "intraokularen" Eingriffs durch das Chandelierlicht hat. Die indirekte Ophthalmoskopie zur Lochsuche entfällt, und der Befund kann bei Betrachtung durch das Mikroskop auch vergrößert dargestellt werden [2] (▶ Abb. 1).…”
Section: Skleraeindellende Verfahrenunclassified